2016
DOI: 10.1007/s12160-016-9865-x
|View full text |Cite
|
Sign up to set email alerts
|

Gender Differences in Relations among Perceived Family Characteristics and Risky Health Behaviors in Urban Adolescents

Abstract: Background Research regarding the role of gender in relations between family characteristics and health risk behaviors has been limited. Purpose To investigate gender differences in associations between family processes and risk-taking in adolescents. Methods Adolescents (N = 249; mean age = 14.5 years) starting their first year at an urban high school in the northeastern U.S. completed self-report measures that assessed family characteristics (i.e., parental monitoring, family social support, family confl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
20
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(25 citation statements)
references
References 41 publications
4
20
0
1
Order By: Relevance
“…The perception of family environment varied by sex of the adolescent, with daughters indicating higher levels of family conflict and lower levels of family cohesion compared to sons. These findings are consistent with those of other studies [55,56]. According to Nelson et al [56], perceived family characteristics differed by gender; female participants reported higher levels of family conflict and parental monitoring, as well as lower levels of family social support.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The perception of family environment varied by sex of the adolescent, with daughters indicating higher levels of family conflict and lower levels of family cohesion compared to sons. These findings are consistent with those of other studies [55,56]. According to Nelson et al [56], perceived family characteristics differed by gender; female participants reported higher levels of family conflict and parental monitoring, as well as lower levels of family social support.…”
Section: Discussionsupporting
confidence: 91%
“…These findings are consistent with those of other studies [55,56]. According to Nelson et al [56], perceived family characteristics differed by gender; female participants reported higher levels of family conflict and parental monitoring, as well as lower levels of family social support. Female adolescents may experience an increased tendency towards interpersonal connectedness and concern for the well-being of others [55], which may cause them to be more sensitive when observing family processes [52].…”
Section: Discussionsupporting
confidence: 91%
“…For instance, having a secure attachment to parents and to peers was a protective factor against early alcohol use but only for girls [ 17 ]. Similarly, among girls only, a higher level of perceived parental monitoring was associated with lower odds of early alcohol consumption [ 18 ]. However, for associations related to the other three domains (individual, school and community), too few data exist to draw robust conclusions on gender-related derterminants.…”
Section: Introductionmentioning
confidence: 99%
“…The levels of serum ALT were higher in boys than in girls, which may relate to the differences in muscle mass and endogenous hormone levels (self-undetermined physical and emotional factors) between genders [36][37][38][39]. In this regard, it is well acknowledged that serum concentrations of estradiol are low in preadolescent girls and increase at menarche [40,41]. The age-related hormonal changes could partly account for the ALT levels that we observed between genders.…”
Section: Prevalence Of Elevated Alt Differed Bymentioning
confidence: 61%